Do not disparage! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Writing from Umberleigh in Devon, England, Trevor Wilson takes us firmly to task and introduces a useful distinction between judgement and implementation. 'Unfortunately some of your authors disparage things about which they clearly know nothing. I...